2020
DOI: 10.1177/1524839920954162
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Cost of Implementing Evidence-Based Interventions to Increase Colorectal Cancer Screening Among an Underserved Population in Chicago

Abstract: With funding from the Centers for Disease Control and Prevention’s Colorectal Cancer Control Program, The University of Chicago Center for Asian Health Equity partnered with a federally qualified health center (FQHC) to implement multiple evidence-based interventions (EBIs) in order to improve colorectal cancer (CRC) screening uptake. The purpose of this study is to determine the effectiveness and cost of implementing a provider reminder system entered manually and supplemented with patient reminders and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This study demonstrated that modest financial incentives, together with patient navigation and patient reminders, can increase FIT kit return rates among a vulnerable rural, largely homeless population. The incremental cost per person screened was also estimated to be within the parameters found in our previous studies (Conn et al, 2020;Kim et al, 2020). The results supplement recommendations of The Community Guide, which recommends multicomponent, evidence-based interventions to promote CRC screening as a key strategy for eliminating disparities in cancer prevention and control (Community Preventive Services Task Force, 2012;Sabatino et al, 2012).…”
Section: Policy and Researchsupporting
confidence: 70%
See 2 more Smart Citations
“…This study demonstrated that modest financial incentives, together with patient navigation and patient reminders, can increase FIT kit return rates among a vulnerable rural, largely homeless population. The incremental cost per person screened was also estimated to be within the parameters found in our previous studies (Conn et al, 2020;Kim et al, 2020). The results supplement recommendations of The Community Guide, which recommends multicomponent, evidence-based interventions to promote CRC screening as a key strategy for eliminating disparities in cancer prevention and control (Community Preventive Services Task Force, 2012;Sabatino et al, 2012).…”
Section: Policy and Researchsupporting
confidence: 70%
“…As noted, the incremental cost was approximately $128 per additional screen at LFC. Our previous research in other settings has shown a wide range of incremental costs per additional CRC screen (Conn et al, 2020;Kim et al, 2020). In rural health centers in West Virginia that were implementing a multicomponent intervention (patient and provider reminders with patient assessment and feedback), we found the average cost per FIT kit returned to be approximately $60 (Conn et al, 2020).…”
Section: > > Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The University of Chicago and Heartland Health Centers in Chicago implemented a provider reminder system based on the electronic medical records but input manually. This intervention, implemented at the health system level, was supplemented with patient reminders and provider assessment and feedback across eight clinic sites (Kim et al, 2020). The California Depart ment of Public Health with its partner, Neighborhood Healthcare, implemented a provider incentive program (payments were offered to support staff at the clinics when predetermined screening targets were met), including patient and provider reminders, to supplement ongoing interventions (Barajas et al, 2020).…”
Section: > > Interventions Crccp Awardees and Partner Clinicsmentioning
confidence: 99%
“…Each study involved multicomponent interventions and offered lessons for successful implementation and scale-up of future programs to increase CRC screening uptake. Details are presented in the accompanying research briefs (Barajas et al, 2020;Conn et al, 2020;Hardin et al, 2020;Kim et al, 2020). Table 2 shows the summary cost data from each study.…”
Section: Screening Uptakementioning
confidence: 99%